"גברא רבה קא אתי": שאיפות לכח על נהרות בבל - הרמן ג'פרי (מחשבת ישראל, 2023)
The Talmudic account of the arrival and reception of Rav in Babylonia is considered alongside a contemporary Manichaean account of Mani’s visit to the royal Sasanian palace, found in the Kephalaia. In both, it is proposed, the new leader is portrayed as posing a threat to the existing power establishment. In both accounts, furthermore, the elevation of the river, and cosmological notions which, it is suggested, are indigenous to Babylonia, play a key role. Indeed, it is through the shared experience and symbolism of the rivers of Babylonia and their interpretation that the inhabitants of the region, both Jewish and Manichaean, convey their fears and hopes, their new tidings and their aspirations.